Sulfanilamide Regulates Flowering Time through Expression of the Circadian Clock Gene LUX. (3rd March 2022) - Hirohata, Atsuhiro; Yamatsuta, Yuta; Ogawa, Kaori; Kubota, Akane; Suzuki, Takamasa; Shimizu, Hanako; Kanesaka, Yuki; Takahashi, Nozomu; Endo, Motomu
Abstract: Flowering time is an agriculturally important trait that can be manipulated by various approaches such as breeding, growth control and genetic modifications. Despite its potential advantages, including fine-tuning the regulation of flowering time, few reports have explored the use of chemical compounds to manipulate flowering. Here, we report that sulfanilamide, an inhibitor of folate biosynthesis, delays flowering by repressing the expression of florigen FLOWERING LOCUS T ( FT ) in Arabidopsis thaliana . Transcriptome deep sequencing and quantitative polymerase chain reaction analyses showed that the expression of the circadian clock gene LUX ARRYTHMO / PHYTOCLOCK1 ( LUX/PCL1 ) is altered by sulfanilamide treatment. Furthermore, in the lux nox mutant harboring loss of function in both LUX and its homolog BROTHER OF LUX ARRHYTHMO (BOA, also named NOX), the inhibitory effect of sulfanilamide treatment on FT expression was weak and the flowering time was similar to that of the wild type, suggesting that the circadian clock may contribute to the FT -mediated regulation of flowering by sulfanilamide. Sulfanilamide also delayed flowering time in arugula ( Eruca sativa ), suggesting that it is involved in the regulation of flowering across Brassicaceae . We propose that sulfanilamide is a novel modulator of flowering.